The Influence Of Capital Structure, Size, Profitability And Liquidity On The Value Of Manufacturing Companies On The Indonesian Stock Exchange For The Period 2018-2022 - Dede Hertina; Amiruddin Amiruddin; Heny Herawati; Alfiana Alfiana; Sri Hastutik (UNIVED Press, 2023)
This research was conducted as a way to analyze the effect of capital structure, size, profitability and liquidity on the value of manufacturing companies listed on the Indonesia Stock Exchange. The population in this study is from 2018 to 2022 using around 200 data taken from around 76 manufacturing companies. This study will show that profitability and capital structure have a significant positive effect on the value of the company. While liquidity does not have a negative significant effect on the value of the manufacturing company. Then for company size, it has a negative significant effect on the value of the manufacturing company. The four variables are subjected to regression testing and also the Fixed Effect Model method or model to obtain the correlation and influence between the independent variables consisting of profitability, capital structure, liquidity and also company size and also the dependent variable, namely company value in this study. From this test, the results are obtained whether or not the results of the analysis and tests are in accordance with the hypotheses of this study.